Estudio de factibilidad para el diseño de un aplicativo en entorno web basado en la herramienta Vuetify, para el control de los procesos administrativos de la Finca “El Manantial” ubicado en la parroquia Ricaurte. - González Moran, Melina Zurelis (2022)
The current case study intends to know the feasibility of presenting the design of an application in a web environment based on the Vuetify tool, for the control of the administrative processes of the "El Manantial" farm located in the Ricaurte parish in Rcto. La Hojita which is from a family environment and allows us to understand the need of yesteryear that said entity suffers in which, in short, everything is carried on paper, this causes the loss of relevant information that the administrator must have to show other owners. ; such as payment to workers, purchase of inputs for cultivation such as cocoa, corn, rice, banana and their price records, that is, how much each of the products was sold respectively, the latter being one of the most important. To carry out the collection of information, the interview was used, the instrument of which was carried out with the administrator in charge of the "El Manantial" farm. On the other hand, the primary objective of the research is to determine the importance of the use of the Library of components Vuetify and Material Design since it helps to work with the JavaScript framework as it is vue.js, in addition, the research was known the technical, operational and economic feasibility study that was of vital interest to test whether it is advisable to design an application in a web environment that adapts to the client intuitively and easy to give a view to the control of the administrative processes of the farm. The case study revealed that the use of libraries that help streamline the process of creating Front End in already known frameworks and never this other give a chance to small reusable components such as Vuetify since it is abstracted from native code.